THE CORRELATION BETWEEN STUDENTS’ ANXIETY DURING CLASS PRESENTATIONS AND THEIR ENGLISH SPEAKING ACHIEVEMENT AT SMA ISLAM AL-MA’ARIF SINGOSARI MALANG - Ilmi Firdaus Aliyah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: This study is aimed to know the correlation between students’ anxiety and their English speaking achievement, and also to discovery the significant difference in the students’ speaking achievement among MIPA1, MIPA2 and MIPA3 classes. This research used correlation design with quantitative approach. The person who takes part in the activity of this research was 72 students from eleventh grade students of MIPA1, MIPA2, and MIPA3 classes in SMA Islam Al-Maarif Singosari. FLCAS questionnaire that consist of 22 items was used to collect data of students’ anxiety and the document of students’ final test score to know their English speaking achievement. The first finding of this study shows there is a negative correlation between students’ anxiety during class presentations and their English speaking achievement, and it is correlated at -0.921 which means the correlation is in a very high correlation. The second finding shows that there was a significant difference on the students’ speaking achievement among three classes.Key words: Correlation, Anxiety, English Speaking Achievement